Exercise capacity in adult patients with congenitally corrected transposition of the great arteries. Issue 2 (1st February 2001) - Fredriksen, P M; Chen, A; Veldtman, G; Hechter, S; Therrien, J; Webb, G
Abstract : OBJECTIVE: To examine cardiopulmonary values, static lung function, and ejection fraction in adult patients with congenitally corrected transposition of the great arteries (CCTGA). PATIENTS AND METHODS: 41 patients who had undergone static lung function testing and cardiopulmonary exercise tests with measurements of ejection fraction were identified at the Toronto Congenital Cardiac Centre for Adults. RESULTS: Aerobic capacity in patients with CCTGA was severely diminished, varying from 30–50% of the results achieved by healthy subjects. Normal values of right ventricular and left ventricular ejection fraction were found. However, the systemic right ventricular ejection fraction increased by 2% from rest to exercise, as opposed to the expected > 5% increase in a healthy population. The pulmonary left ventricular ejection fraction decreased by 2% at peak exercise. CONCLUSION: Diminished values of heart rate, forced expiratory volume in one second (FEV1 ), forced vital capacity, and systolic blood pressure compared to the predicted values may contribute to the reduced maximal oxygen uptake (Vo 2 max) found in patients with CCTGA. In addition, a limited increase in systolic right ventricular ejection fraction and a decrease in pulmonary left ventricle contractility suggest a dysfunction of both ventricles.